Saving living diversity in the face of the unstoppable 6th mass extinction: a call for urgent international action - Fred Naggs (The White Horse Press, 2017)
The global scale and impact of current and increasing human population size is incompatible with the survival of biological diversity and the 6th mass extinction cannot be stopped. For the vast majority of species we have neither the knowledge of when they will go extinct nor the capacity to find out. Conventional conservation measures can only amount to token damage limitation. Advances in molecular biology allow low cost options for storing the genetic diversity of numerous species and maximising future options for restoring species.